Effect of Nitrogen and Zinc Application on Nickel, Lead and Cadmium Contents of Maize Plant in Typic Xerochrept and Calcixeroll Soils - Adiloglu, Sevint; Adiloglu, Aydin (Asian Journal of Chemistry, 2010)
This research was carried out in order to determine the effects of nitrogen and zinc fertilizers on the nickel, lead and cadmium contents of maize plant in typic xerochrept and typic calcixeroll soils. The experiment was done in greenhouse conditions with three replications and maize plant was grown. Three different doses of N (N0:0; N1:50 and N2:100 kg N ha-1) were applied to each pot as NH4NO3. Four different doses of Zn (Zn0:0; Zn1:5; Zn2:10 and Zn3:20 mg kg-1) were applied to each pot as ZnSO4·7H2O. According to the results, dry matter amount and Ni content of maize plant increased with increasing of N and Zn doses. Lead and Cd contents of maize plant decreased with increasing of N and Zn application doses. Increasing of dry matter amount and Ni content and decreasing of Pb and Cd contents of maize plant were determined significant at the level of 1 %, statistically.